Information-Aggregation Bias - Goodfriend, Marvin (American Economic Review, 1992)
Aggregation in the presence of data-processing lags distorts the information content of data, violating orthogonality restrictions that hold at the individual level. Though the phenomenon is general, it is illustrated here for the life-cycle–permanent-income model. Cross-section and pooled-panel data induce information-aggregation bias akin to that in aggregate time series. Calculations show that information aggregation can seriously bias tests of the life-cycle model on aggregate time series, cross-section, and pooled-panel data.